Antibacterial Activity of Mango Gedong Gincu Peel Fraction in Inhibiting the Growth of Staphylococcus aureus - Rama Samara Brajawikalpa; Robi'atul 'Adawiyah (Indonesian Journal of Applied Research (IJAR), 2025)
Gedong Gincu Mango peel (Mangifera indica L.) contains a variety of secondary metabolites, including flavonoids, tannins, saponins, alkaloids, and terpenoids. These compounds play a crucial role in self-defence and exhibit significant pharmacological activity, particularly as antibacterial agents. The purpose of this study is to identify the content of secondary metabolite compounds of each fraction based on its polarity properties, and to determine the inhibitory power of Staphylococcus aureus ATCC 25293 bacteria. This study is experimental research with a post-test only control group. This study used 2 control groups and 12 treatment groups consisting of n-hexane, ethyl acetate, and butanol fractions with concentrations of 6.25%, 12.5%, 25%, 50% respectively and repeated 3 times. The antibacterial test was carried out by the well diffusion method, which was repeated 3 times on the MHA medium, and the inhibition zone was measured. The study showed that the n-hexane fraction contained alkaloids, steroids, and saponins, while the ethyl acetate and butanol fractions contained flavonoids, alkaloids, tannins, triterpenoids, and phenolics. A 50% concentration produced the greatest inhibition zone in all fractions, with mean values of 8.05 mm (moderate) for n-hexane, 15.41 mm (strong) for ethyl acetate, and 12.16 mm (strong) for butanol. The 50% ethyl acetate fraction was the most effective in inhibiting the growth of Staphylococcus aureus ATCC 25923.